Sharia banking dispute resolution in Indonesia after the verdict of the constitutional court no. 93/puu-x/2012 - WINARSI, SRI; THALIB, PRAWITRA; HAJATI, SRI; KHOLIQ, MOHAMAD NUR (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT Constitutional Court has issued a verdict No. 93/PUU-X/2012 that repeal and declare the provisions of Article 55 paragraph 2 of the law No. 21 year 2008 on Sharia banking null and void. The method used in drafting this article is normative research using a conceptual and statutory approach, which results in the conclusion that due to the principle of Sharia banking operations differ from conventional banking, the procedure for the settlement of the dispute must also be different, which in this case is the religious court. RESUMEN El Tribunal Constitucional ha emitido un veredicto No. 93 / PUU-X / 2012 que deroga y declara nula y sin efecto las disposiciones del artículo 55 párrafo 2 de la ley No. 21 del año 2008 sobre la banca Sharia. El método utilizado en la redacción de este artículo es una investigación normativa con un enfoque conceptual y estatutario, lo que da como resultado la conclusión de que debido al principio de la Sharia, las operaciones bancarias difieren de la banca convencional, por lo que el procedimiento para la solución de la controversia también debe ser diferente, que en este caso se trata en el tribunal religioso.